The Lysis of Artificial Thrombi - Metcalf, Michael J (Thrombosis and Haemostasis, 1980)
The susceptibility to lysis of artificial thrombi formed from native rabbit blood in the presence or absence of dextran was determined using the Chandler loop technique. Thrombi of identical weight were formed in the presence of saline or dextran and when spontaneous thrombolysis was allowed to take place, thrombi formed in the presence of dextran 70 were lysed to a greater extent than those formed under control conditions.The possible factors influencing this observation were studied. Increasing concentrations of streptokinase increased the extent of thrombolysis in both control and dextran treated thrombi. Maximal streptokinase induced thrombolysis occurred in the presence of a 2 per cent final concentration of dextran Mw 40,000 and 500,000 and dextran 70 at a final concentration of 1.2 per cent.Increased thrombolysis was not observed when albumin was substituted for dextran.Finally, similar observations were recorded for streptokinase induced thrombolysis using human blood.
Keywords: Thrombolysis; Chandler loop; Dextran 70